Micropropagation protocol for Syngonanthus elegans (Bong.) Ruhland: an ornamental species - Pêgo, Rogério Gomes; Paiva, Patrícia Duarte de Oliveira; Paiva, Renato (Acta Scientiarum. Agronomy, 2014)
The research aimed to establish a protocol of micropropagation of Syngonanthus elegans. Seed germination in WPM media containing 0%, 25%, 50%, 75% and 100% salt concentrations was evaluated. Establishment of plantlets in WPM and MS media, with 50% or 100% salt concentrations, was studied. The addition of 0, 5, 10, 15, 20, 25 and 30 g L-1of sucrose in WPM media was evaluated. The effects of TDZ (0.0; 0.5; 1.0; 2.0 and 4.0 mg L-1) and ANA (0.0; 0.5 and 1.0 mg L-1) in all possible combinations were investigated. To test acclimatization, sand, PlantmaxTM or vermiculite substrates were evaluated by direct acclimatization and pre-acclimatization. The germination of S. elegans seeds was not influenced by salt concentration in the culture media, but the germination speed was affected. The WPM medium with 17 g L-1 of sucrose is recommended for establishment of plantlets. Callus formation occurs in presence of 0.5 or 1.0 mg L-1 of NAA, in absence of TDZ, or when same concentrations of NAA and TDZ were added. Sprouts were most frequently produced when 0.5+0.5 mg L-1 or 1.0+1.0 mg L-1 of NAA and TDZ were used. The S. elegans plants had survival rate was 25.6% after acclimatization.